Outcome of patient with myasthenia gravis with the use of immunotherapy in metastatic Merkel cell carcinoma. Issue 2 (19th February 2022) - Williams, Sarah; Liang, Christina; Guminski, Alexander; Hruby, George; Chan, David
ABSTRACT: We report on a 79-year-old man diagnosed with localized Merkel cell carcinoma (MCC) who also had acetylcholine receptor antibody (Ach-R-Ab)-positive myasthenia gravis (MG) controlled on prednisolone, mycophenolate and intravenous immunoglobulin (IVIG). His MCC was initially treated with radiation, followed by chemotherapy on metastatic recurrence. Chemotherapy initially stabilized the disease, but he experienced significant fatigue and his disease progressed within 3 months. After careful consideration of the risk of a myasthenic crisis, he was commenced on avelumab. He had initial partial response, though he ultimately developed progressive disease which led to a decision for best supportive care at 10 months post starting immunotherapy. Importantly, as per spirometry, his MG remained stable throughout immunotherapy. We present the current case to demonstrate that MG should not be viewed as an absolute contraindication to immunotherapy in scenarios where there are limited alternate therapeutic options.